Acute kidney injury and ANCA positivity in a patient treated with glecaprevir/pibrentasvir: a case report - Kwon, Lawrence Hyun; Griffiths, Jennifer; DiFranza, Lanny (Frontiers in Medicine, 2025)
Background: Glecaprevir/pibrentasvir is an effective antiviral therapy for hepatitis C virus infection and is generally regarded safe in patients with renal impairment. However, renal complications are a notable, albeit rare, concern.Case Presentation: We report a case of acute kidney injury in a man in his 50s with chronic hepatitis C virus, chronic obstructive pulmonary disease, morbid obesity, a history of heroin dependence, and untreated type 2 diabetes mellitus. About four weeks into an eight-week glecaprevir/pibrentasvir regimen he developed progressive lower extremity edema, bullae, and skin ulcers with worsening renal function. His serum creatinine rose to 4.46 mg/dL and blood urea nitrogen to 44 mg/dL. ANCA serology revealed dual perinuclear and cytoplasmic positivity, though anti-proteinase 3 and anti-myeloperoxidase antibody tests were negative. Kidney biopsy revealed diffuse tubulointerstitial injury with erythrocyte casts indicative of glomerular bleeding into the distal nephrons, though without glomerular crescent formation.This case illustrates the potential for glecaprevir/pibrentasvir to induce acute kidney injury, acute interstitial nephritis and possibly ANCA-associated vasculitis. Recognizing these adverse renal effects is critical for making timely diagnosis and management in hepatitis C virus patients undergoing antiviral therapy.